Mapping RNA‐seq Reads with STAR. Issue 1 (3rd September 2015) - Dobin, Alexander; Gingeras, Thomas R.
Abstract: Mapping of large sets of high‐throughput sequencing reads to a reference genome is one of the foundational steps in RNA‐seq data analysis. The STAR software package performs this task with high levels of accuracy and speed. In addition to detecting annotated and novel splice junctions, STAR is capable of discovering more complex RNA sequence arrangements, such as chimeric and circular RNA. STAR can align spliced sequences of any length with moderate error rates, providing scalability for emerging sequencing technologies. STAR generates output files that can be used for many downstream analyses such as transcript/gene expression quantification, differential gene expression, novel isoform reconstruction, and signal visualization. In this unit, we describe computational protocols that produce various output files, use different RNA‐seq datatypes, and utilize different mapping strategies. STAR is open source software that can be run on Unix, Linux, or Mac OS X systems. © 2015 by John Wiley & Sons, Inc.